Alternate-day fasting differentially affects body composition, metabolic and immune response to fasting in male rats exposed to early-life adversity: Modulatory role of cafeteria diet - Sara C. Sagae; Edson D. R. Paz; Bárbara Zanardini; Ana Claudia Amaral; Gabriela A. Bronczek; Patrícia Koehler-Santos; Jarbas R. de Oliveira; Celso R. Franci; Márcio V. F. Donadio; Parker J. Holman; Charlis Raineki (PLoS ONE, 2025)
The increased risk for obesity and metabolic disorders following early-life adversity is aggravated by poor diet (e.g., cafeteria diet). Alternate-day fasting (ADF) is a dietary regimen shown to improve immune and metabolic dysfunction related to obesity. Here, we evaluate if ADF can ameliorate the negative effects of early-life adversity and/or cafeteria diet on biological, immune and metabolic parameters. At weaning, animals reared under normal or adverse conditions (i.e., low bedding) were fed either standard chow or cafeteria diets ad libitum or subjected to an ADF regimen. In adulthood, we measured 24-hour fasted cholesterol, triglycerides, cytokines, oxidative stress markers, and body composition parameters including perigonadal, retroperitoneal, and brown fat pad weight. Animals exposed to early-life adversity respond differently to cafeteria diet and ADF. Adverse reared animals fed chow diet in the ADF regimen showed the largest reduction in body weight and perigonadal and retroperitoneal fat pad weight, the smallest increase in corticosterone levels, and the largest increase in TNF-α levels. However, the differential effects of the ADF regimen on body, perigonadal and retroperitoneal fat weight observed in adversely reared animals fed chow diet compared to controls were not present if the adversely reared animals were fed cafeteria diet in the ADF regimen. Furthermore, adversely reared animals fed cafeteria diet in the ADF regimen showed high IL-1β and IL-6 levels. Together, the data suggest that the altered vulnerability to metabolic and immune dysfunction following early-life adversity is not just due to the type of diet but also how the diet is consumed.